Proterozoic East Gondwana supercontinent assembly and breakup - Dasgupta S; Windley B F; Yoshioa M (London Geology Society, 2003)
This volume focuses on late Mesoproterozoic to early Cambrian events related to Gondwana assembly and break up. The nineteen papers of this volume provide a comprehensive review including advanced knowledge and new data from all critical areas of East Go
Keywords: East Gondwana; Proterozoic era